Advanced Accounting (Book). - Winter, Sidney G.; Thomas, Wm. E. (The Accounting Review, 1944)
Abstract Reviews the book "Advanced Accounting," by Howard S. Noble, Wilbert E. Karrenbrock and Harvey Simons.